Safety Aspects of Single-Lane Roundabout Management Systems in Connected Vehicles Environments - Mădălin-Dorin POP; Cătălin Constantin NICULESCU; Octavian PROȘTEAN; Gabriela PROȘTEAN (Communications of International Proceedings, 2021)
The availability of maturing and heavily evolving embedded systems can contribute to roads by adding physical infrastructures like high-speed internet, sensors, solar panels, and many others to transform them into smart roads. Technologies like Vehicle-to-Infrastructure (V2I) communication, Autonomous Vehicles and Connected Vehicles (CV/AV/CAV) represent the most attractive automotive technologies nowadays, and they continue to emerge and rapidly acquire new capabilities. The existence of CV/AV/CAV environments will significantly increase vehicle safety and improve traffic mobility, efficiency, and sustainability. The latest designed traffic management systems for roundabouts consider the roundabout as a system that provides CV/AV/CAV with optimal trajectories to negotiate the roundabout, maximize throughput, and minimize control delay in real-time. However, these roundabouts managers have as main drawback the neglection of disturbances like the road conditions (wet road, ice, snow), unreasonable situations due to improper speed or behavior of the CAVs, or comfort inside a CAV. This research performs a risk identification from the functional safety point of view by applying the ISO 26262 and ISO 21448 requirements to the existing researches. It describes what disturbances on the roundabout manager of the single-lane roundabout could lead to failure. The main outcome of this study is to provide a set of measures to address the disturbances from CV environments and, implicitly enhance safety for the particular case of single-lane roundabouts.
Keywords: Connected Vehicles; ITS; Risk Assessments; Roundabouts; Safety; Sensors.